2004
DOI: 10.1002/elps.200406059
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental aspects of contactless conductivity detection for capillary electrophoresis. Part I: Frequency behavior and cell geometry

Abstract: A better understanding of the characteristics of the axial contactless conductivity cell could be obtained by carefully studying the effect of the cell geometry on its frequency behavior. A good fit between theoretical and experimental results shows that the axial contactless conductometric detector can effectively be described by the simplest possible equivalent circuitry consisting of a capacitor, resistor, and a second capacitor. The cell constant is largely defined by the length of the gap between the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 40 publications
5
97
0
2
Order By: Relevance
“…Each solution was then consecutively injected six times into the CE-C 4 D systems and analytical parameters were calculated for each detector, which are summarized in Table 1. The settings of the excitation voltage, frequency, gain and other parameters were individually optimized to achieve best signal-to-noise characteristics [6] and are also summarized in Table 1. The relative standard deviation (RSD) values of migration times and peak areas are given for the 200 mM concentration level for six consecutive injections (n ¼ 6).…”
Section: Determination Of Inorganic Cations In a Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…Each solution was then consecutively injected six times into the CE-C 4 D systems and analytical parameters were calculated for each detector, which are summarized in Table 1. The settings of the excitation voltage, frequency, gain and other parameters were individually optimized to achieve best signal-to-noise characteristics [6] and are also summarized in Table 1. The relative standard deviation (RSD) values of migration times and peak areas are given for the 200 mM concentration level for six consecutive injections (n ¼ 6).…”
Section: Determination Of Inorganic Cations In a Lowmentioning
confidence: 99%
“…This presumably is due to Joule heating and not an immediate feature of the detectors. The peak distortions for the detector with the miniaturized cell which have become apparent for the high conductivity buffer must be due to the relatively low operating frequency that has to be employed for this detector [6]. The salient performance parameters for quantifications in both electrolyte solutions are summarized in Table 2.…”
Section: Determination Of Inorganic Cations In Medium Andmentioning
confidence: 99%
“…It has been found for classical CE detectors with tubular and semitubular electrodes [13,14] that the measurable AC current only flows between certain parts of the electrode surfaces, called the effective surfaces that are closest to one another (effective electrode widths). There is no reason to assume that it is different with the present wire detector cells and the present model calculations actually confirm this assumption, indicating that only those parts of the electrode surfaces are active that are oriented against one another (they "see" one another), as represented by the shaded areas in Figs.…”
Section: Model Of the Detection Cellsmentioning
confidence: 99%
“…Furthermore, the method is inexpensive. Although a relatively recent introduction, detailed studies of the influence of the cell design and its operating parameters on the performance of the C 4 D have been carried out and its functioning is well understood [29][30][31][32][33]. Recent reviews, which give an overview of the reported applications of the C 4 D, are available [34,35].…”
Section: Introductionmentioning
confidence: 98%